Bulk Structure Elucidation: Computational Spectroscopy of Ionic Liquids for Bulk Structure Elucidation (Adv. Theory Simul. 10/2018). Issue 10 (4th October 2018) - Saielli, Giacomo
Abstract : "Those who have knowledge, don't predict. Those who predict, don't have knowledge" – Lao Tzu. We do not have a detailed knowledge of the microscopic structure of ionic liquids; yet, in article number1800084, Giacomo Saielli validates the proposed structures with the prediction, by quantum chemistry, of the spectroscopic signatures of the bulk phase, thus gaining knowledge through prediction.